THE CORRELATION OF NUTRITION STATUS WITH THE ACTIVITY OF PRESCHOOL CHILDREN IN PAMULIHAN VILLAGE, CILACAP JAWA TENGAH - Rensi Rahmawati; Nurti Yunika Kristina Gea; Lina Indrawati; Lisna Agustina; Lisna Nuryanti; Roulita Roulita (NHM PRESS, 2023)
Introduction: The purpose of this study was to determine the correlation of nutrition status with the activity of preschool children. The population is the parents who have preschool children. Samples were obtained by purposive sampling. The research was conducted in July. Analysis of the data used is SPSS. Based on the calculation, the calculated value is 0,014 with a significant value of 0,05 (p<0,05). The conclusion is that there is a correlation between nutritional status and The activity of preschool children in Pamulihan village, Cilacap Jawa Tengah.